VARIASI PENAMBAHAN TEPUNG UMBI DAHLIA DALAM MINUMAN SINBIOTIK SARI JAGUNG MANIS MENGGUNAKAN ISOLAT Lactobacillus casei subsp. casei R-68 - Aris Setiawan; Usman Pato; Akhyar Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to study the addition of various of dahlia tuber flour in making sinbiotic drink of sweet corn extract by using Lactobacillus casei subsp. casei R-68 which isolated from dadih. The research was carried out experimentally using a Completely Randomized Design with 4 treatments and 4 replications thus obtaining 16 experimental units.Data yang diperoleh dianalisis secara statistik dengan menggunakan analisis sidik ragam (ANOVA). The data found were statistically analyzed using Analysis of Variance (ANOVA). Jika F hitung lebih besar atau sama dengan F tabel maka dilanjutkan dengan uji DNMRT pada taraf 5%.If the F count is greater than or equal to F table then continued with DNMRT test at 5% level. The results of the present study indicate that initial pH of sinbiotic drink of sweet corn extract were 3.73-3.85, total lactic acid 0.69-0.96%, total LAB 9.90-10.80 log cfu/ml after fermentation, total solid 10.30-14.55%, protein 1.14-1.91% and fiber 0.10-0.21%. The results show that the addition of dahlia tuber flours significantly affected the pH, total lactic acid, total LAB, total solid, protein and fiber contens as well as sensory evaluation of sinbiotic drink of sweet corn extract. Overall acceptance test indicated that the panelists were “rather like” for sinbiotic drink of sweet corn extract. The best treatment based on the number of LAB, protein contant as well as sensory evaluation was treatment SJ2 (addition 3% concentration of dahlia tuber). Keywords: Prebiotic, probiotic, dahlia tuber flour, Lactobacillus casei subsp. casei R-68